Handling Big Data of Alien Species in Europe: The European Alien Species Information Network Geodatabase - Deriu, Ivan; D’Amico, Fabio; Tsiamis, Konstantinos; Gervasini, Eugenio; Cardoso, Ana Cristina (Frontiers in ICT, 2017)
Building and managing large datasets of alien species is crucial to research, management and control of biological invasions. To this end, the European Alien Species Information Network (EASIN) platform aggregates, integrates and harmonizes spatio-temporal data regarding alien species in Europe, including both invasive and non-invasive alien species. These data are stored in the EASIN Geodatabase after their harvesting from relevant sources in the frame of a global and European databases partnership and scientific literature. The ownership of the data remains with its source, which is properly cited and linked. The process of data harvesting is performed through the EASIN Data Broker system, which retrieves the information related to alien species data in Europe and stores them in a normalized database structure. Data are subsequently refined through validation, cleansing and standardization processes and finally stored in the EASIN Geodatabase. All data are finally visualized and shown in occurrence maps at different levels of spatial visualization. Analysis of the data contained in the EASIN Geodatabase through flexible web services offered by the system has already provided useful input in scientific works and policies on biological invasions. Data from European Union (EU) member state official surveillance systems, within the framework of the EU Regulation 1143/2014 on Invasive Alien Species, are expected to contribute to the update of the EASIN Geodatabase. In addition, data from citizen science initiatives will further enrich the Geodatabase after appropriate validation. In this article we describe and discuss the technical aspects, data flow and capabilities of the EASIN Geodatabase.